BS EN 62496-4-3 Ed.1.0. Optical circuit boards. Part 4-3. Interface standards. Terminated waveguide OCB assembly using a single-row thirty-two-channel PMT connector intermateable with 250 μm pitch MPO 16 (16th November 2020) - British Standards Institution,
No abstract available